2021
DOI: 10.1371/journal.pone.0249907
|View full text |Cite
|
Sign up to set email alerts
|

Saturated free fatty acids induce placental trophoblast lipoapoptosis

Abstract: Introduction Obesity during pregnancy increases the risk for maternal complications like gestational diabetes, preeclampsia, and maternal inflammation. Maternal obesity also increases the risk of childhood obesity, intrauterine growth restriction (IUGR) and diabetes to the offspring. Increased circulating free fatty acids (FFAs) in obesity due to adipose tissue lipolysis induces lipoapoptosis to hepatocytes, cholangiocytes, and pancreatic-β-cells. During the third trimester of human pregnancy, there is an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Additionally, pathways associated with the production of the monosaturated fatty acid palmitoleate were increased in the microbiome of pregnant individuals. Palmitoleate has been shown to play an important role in the maintenance of placental trophoblasts by preventing apoptosis ( 48 ). We also observed increased enrichment of GO terms associated with the transportation of simple sugars like lactate, glucose, and galactose in late pregnancy compared to the GO terms in postpartum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pathways associated with the production of the monosaturated fatty acid palmitoleate were increased in the microbiome of pregnant individuals. Palmitoleate has been shown to play an important role in the maintenance of placental trophoblasts by preventing apoptosis ( 48 ). We also observed increased enrichment of GO terms associated with the transportation of simple sugars like lactate, glucose, and galactose in late pregnancy compared to the GO terms in postpartum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 presents volcano plots of the odds ratio (OR) distributions for each maternal metabolite according to the faltering growth and early accelerating growth phenotypes estimated from logistic regression analysis, adjusted for maternal age and newborn sex. These phenotypes were associated with 709 statistically significant maternal metabolites with positive effect for the faltering growth phenotype and 54 metabolites (appendix pp [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] for the early accelerating growth phenotype, and 31 statistically significant maternal metabolites with negative effect for the faltering growth phenotype and 76 metabolites (appendix pp 43-45) for the early accelerating growth phenotype (figure 4A and B). 33 metabolites (appendix p 46) overlapped between the falter ing growth and early accelerating growth phenotypes, which were also associated with 627 (for the faltering growth phenotype) and 1675 (for the early accelerating growth phenotype) statistically significant umbilical cord venous metabolites with positive effect.…”
Section: Resultsmentioning
confidence: 99%
“…Palmitoleate decreases fat deposition in the liver and enhances insulin sensitivity [57]. Studies have shown that palmitoleate protects against free fatty acid-induced hepatocyte lipoapoptosis [23] and trophoblast lipoapoptosis [59], respectively. Supplementation of palmitoleate has shown to be effective against non-alcoholic fatty liver disease and atherosclerosis in mouse models [60,61].…”
Section: Discussionmentioning
confidence: 99%